Iterative Methods for Equality-Constrained Least Squares Problems - Barlow, J. L.; Nichols, N. K.; Plemmons, R. J. (SIAM journal on scientific and statistical computing, 1988)
We consider the linear equality-constrained least squares problem (LSE) of minimizing ${\|c - Gx\|}_2 $, subject to the constraint $Ex = p$. A preconditioned conjugate gradient method is applied to the Kuhn-Tucker equations associated with the LSE problem. We show that our method is well suited for structural optimization problems in reliability analysis and optimal design. Numerical tests are performed on an Alliant FX/8 multiprocessor and a Cray-X-MP using some practical structural analysis data.